3x-9=3x-3

Simple and best practice solution for 3x-9=3x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-9=3x-3 equation:


Simplifying
3x + -9 = 3x + -3

Reorder the terms:
-9 + 3x = 3x + -3

Reorder the terms:
-9 + 3x = -3 + 3x

Add '-3x' to each side of the equation.
-9 + 3x + -3x = -3 + 3x + -3x

Combine like terms: 3x + -3x = 0
-9 + 0 = -3 + 3x + -3x
-9 = -3 + 3x + -3x

Combine like terms: 3x + -3x = 0
-9 = -3 + 0
-9 = -3

Solving
-9 = -3

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -196=7x+7(5x+14) | | 525+.21x= | | 1-(1-6m/7) | | (y^2x)*(y^2)-4(y^3)=0 | | 5x-5(4x+31)=-290 | | 43+x=253 | | 3y*3= | | 2(6x-4)=4(5x+3) | | 16y^2-3y+2.25=0 | | log(25x)-log(x-1)=2 | | 360=128+128+52+6x-8 | | -41+4x=79 | | log(b)=0.31 | | 5s+2r+6-3r-2= | | 2(4x-1)=3(3x-5) | | 8(-10x+21)=728 | | -32=0 | | -6c=-6 | | .4*x+150=x | | 180=5x-9+106+33 | | (X^2)*lnx=0 | | 6.25w=68.75 | | 16y^2-3y-16=0 | | -11x-7x+29=-14x+34 | | 3=8x+11+8 | | -7y+17-12y=-38 | | 1x-3+2x= | | x+14y+35=0 | | 16y^2-3y+16=0 | | 9-2n=29 | | s=4pier^2 | | 4/g-1=2 |

Equations solver categories